Hospital Governance and Appropriation of User Services by Medical and Social Staff: The Case of the Douala-Cameroon Hospitals (Global Journal of Management and Business Research, 2022)
Abstract not found
Keywords: hospital governance - ownership of user services - medical and social staff - patients - douala hospital – Cameroon